On features and measures of psychological wellbeing - Shevleva, Olga; Cordasco, Gennaro; Vogel, Carl; Esposito, Anna (My University, 2022)
Low levels of psychological wellbeing pose considerable burdens on society in terms of mortality, unemployment, absen- teeism, medications, social services, morbidity, and in-out patients’ costs. Early detection and preventive treatments may help to reduce costs and improve quality of life. Researchers have proposed several measures and tried to identify new measures of psychological wellbeing, but there is not a universally accepted measure, and all the existing ones have their own limitations. This paper discusses research results focusing on behavioral, psychological, social, demographic features and biomarkers of psychological wellbeing and mental disorders associated with low psychological wellbeing levels. The features which are addressed in the paper are categorized into three groups: affecting features, features for therapy and detecting features. This categorization is described and defended.
Keywords: Psychological Wellbeing; Subjective Wellbeing; Mental Health; Psychological Wellbeing Features; Inclusive Society; Computational Linguistics; Computational linguistics; Health and Well being; Health and Well-being; computational linguistics